Genetic causal beliefs and developmental context: Parents' beliefs predict psychologically controlling approaches to parenting. (November 2022) - Nyman, Tristin; Stichter, Matthew; Rivera, Grace N; Maffly-Kipp, Joseph; Brooker, Rebecca J; Vess, Matthew
We examined the association of parents' genetic causal beliefs and parenting behaviors, hypothesizing a positive association between parents' genetic causal beliefs and their use of psychological control. Study 1 ( N = 394) was a cross-sectional survey and revealed that parents' genetic essentialism beliefs were positively associated with their self-reported use of harsh psychological control, but only for parents who reported relatively high levels of problem behaviors in their children. Study 2 ( N = 293) employed a 4-day longitudinal design and revealed that parents' genetic causal beliefs positively predicted the use of psychological control, especially on days when they perceived relatively high problem behaviors in children. Overall, the studies demonstrated that parents' genetic causal beliefs about character positively predicted psychologically controlling and harsh responses to child problem behaviors, which may ultimately be detrimental to child development.